Conserving rainforests - Banks, Martin (Italy : Wayland, 1990)
Describes the rapidity with which the rain forests of the world are being destroyed, the harm to plants, animals, and humans, and remedies for preserving the rain forests.
Includes index and glossary.
Keywords: Rain forest ecology -- Juvenile literature; Forest conservation -- Juvenile literature; Rain forest ecology